The Role of Noncoding RNA Pseudouridylation in Nuclear Gene Expression Events - Zhao, Yang; Dunker, William; Yu, Yi-Tao; Karijolich, John (Frontiers in Bioengineering and Biotechnology, 2018)
Pseudouridine is the most abundant internal RNA modification in stable noncoding RNAs. It can be catalyzed by both RNA-dependent and RNA-independent mechanisms. Pseudouridylation impacts both the biochemical and biophysical properties of RNAs and thus influences RNA-mediated cellular processes. Investigation of nuclear noncoding RNA pseudouridylation has demonstrated that is critical for the proper control of multiple stages of gene expression regulation. Here we review how nuclear noncoding RNA pseudouridylation contributes to transcriptional regulation and pre-mRNA splicing.